2016
DOI: 10.1038/leu.2016.252
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy with decitabine in younger adults with acute myeloid leukemia in first remission: a phase 2 Cancer and Leukemia Group B Study (CALGB 10503)

Abstract: In this prospective phase 2 clinical trial conducted by Cancer and Leukemia Group B (CALGB, now the Alliance), we studied decitabine as maintenance therapy for younger adults with acute myeloid leukemia (AML) who remained in first complete remission (CR1) following intensive induction and consolidation. Given that decitabine is clinically active in AML and with hypomethylating activity distinct from cytotoxic chemotherapy, we hypothesized that one year of maintenance therapy would improve disease-free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…Within each age group, patients were treated similarly, receiving a cytarabine/anthracyclinebased induction on Cancer and Leukemia Group B (CALGB) trials. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] No patient received an allogeneic stem cell transplant in first CR. Details of CALGB treatment protocols are provided in the Online Supplementary Appendix and Online Supplementary Table S1.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…Within each age group, patients were treated similarly, receiving a cytarabine/anthracyclinebased induction on Cancer and Leukemia Group B (CALGB) trials. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] No patient received an allogeneic stem cell transplant in first CR. Details of CALGB treatment protocols are provided in the Online Supplementary Appendix and Online Supplementary Table S1.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…One‐year and 3‐year DFS were 79% and 54%, and 1‐year and 3‐year OS were 96% and 68%, respectively. Patients with core bind factor (CBF) AML, showed a 1‐year DFS of 80%, while non‐CBF AML patients had 1‐year DFS of 78%; no significant difference was observed between the two groups …”
Section: Trials Including Maintenance Therapy After Consolidation Inmentioning
confidence: 99%
“…The study had 23 patients aged ≥60 years with high‐risk MDS, or AML following MDS, and showed no DFS or OS benefit . Also, assessment of survival with decitabine (20 mg/m 2 × 5 days every 6 weeks for 8 cycles) in patients aged <60 years with AML in CR after consolidation therapy showed no benefit in terms of DFS and OS when compared with historical controls …”
Section: Post‐remission Treatment Approachesmentioning
confidence: 99%